Viability of shorea resinosa foxw excisedembryos following dehydration technique - Asrol Hadri, Bin Radzuan. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This study was carried out to assess the viability of cryopreserved excised-embryos of Shorea resinosa Foxw that treated using dehydration technique. Embryos sources were of high quality, where initial moisture content and germination of were 64.9 % and 73 % respectively, and Viability of the excisedembryos was 93 % when assessed using 0.5 % of tetrazolium for 90 minutes. Results showed that using MS medium with several modifications of composition especially in composition of Macronutriet composition which gave 73% ofgermination. The best treatment was obtained from dehydration of excised embr}Qs with 0.4 M concentration of sucrose for 90 minutes which gave viability of 82 % and exposing excised-embryOs with silica gel by 3 hours which gave 70 %. This result was useful for expand the studies in storage an preserve the embryos in liquid nitrogen